ChemInform Abstract: A Ligand‐Controlled Switch of Regioselectivity in Ring‐Opening Coupling of Diarylmethylenecyclopropa[b]naphthalenes with Grignard Reagents. Issue 20 (April 2016) - Cao, Jian; Huang, Xian; Wu, Luling
Abstract: A Pd(OAc)2 catalyzed highly regioselective ring‐opening coupling reaction of diarylmethylenecyclopropa[b]naphthalenes and Grignard reagents to provide differently substituted β‐vinylic naphthalenes is developed.